Предмет: Алгебра, автор: esminakaraosman15

помогите пожалуйста

Приложения:

Ответы

Автор ответа: Universalka
0

\displaystyle\bf\\\frac{Sin(\alpha +40^\circ)-Cos\alpha \cdot Sin40^\circ}{Cos\alpha \cdot Cos40^\circ} =\\\\\\=\frac{Sin\alpha\cdot Cos40^\circ+Cos\alpha\cdot  Sin40^\circ-Cos\alpha \cdot Sin40^\circ}{Cos\alpha \cdot Cos40^\circ} =\\\\\\=\frac{Sin\alpha \cdot Cos40^\circ}{Cos\alpha \cdot Cos40^\circ} =\frac{Sin\alpha }{Cos\alpha } =tg\alpha

Похожие вопросы
Предмет: Английский язык, автор: nikitakluyev364